Signal transmission control cable with high shielding performance
By introducing the synergistic effect of iron-cobalt alloy and nickel-cobalt silicon fibers into the control cable, combined with the porous structure design, the electromagnetic shielding and impact resistance of the cable are improved, and the problem of insufficient shielding and impact resistance in the existing technology is solved, and is suitable for signal transmission in complex electromagnetic environments.
Patent Information
- Application Number
- CN202510388793.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-04
AI Technical Summary
The shielding and impact resistance of existing control cables need to be further improved, especially the synergistic enhancement effect of carbon nanotubes and graphene is limited, and the nickel-plated glass microbeads are too rigid and easily broken.
The conductive layer is formed by twisting silver-clad copper conductors, combining the composite polyvinylidene fluoride insulating layer, flexible shielding foam shielding layer and composite polypropylene outer sheath layer, and the synergistic effect of iron-cobalt alloy and nickel-cobalt silicon fibers is formed to enhance electromagnetic shielding performance, and the impact force is dispersed through structural design to improve impact resistance and tensile resistance.
It realizes efficient shielding of broadband electromagnetic waves, enhances the flexibility and impact resistance of the cable, and is suitable for signal transmission in complex electromagnetic environments.
Smart Images

Figure CN120261032A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic shielding materials, and in particular to a control cable for signal transmission with high shielding performance. Background Art
[0002] The development of electromagnetic shielding cables has gone through several stages, focusing mainly on improving electromagnetic shielding performance and impact resistance. The initial cables used a single-layer metal shielding layer, which could isolate certain electromagnetic interference, but the effect was limited. With the advancement of technology, multi-layer shielding structures came into being, combining braided layers and aluminum foil layers to greatly improve the cable's ability to resist electromagnetic interference. In modern times, the addition of absorbing materials further enhances the shielding effect, allowing the cable to work stably in more complex electromagnetic environments. At the same time, impact resistance has gradually received attention. Early cables mainly resisted impact through basic outer sheath design, while modern cables use high-strength polymer composites and intelligent materials to improve impact and wear resistance.
[0003] For example, the prior art CN111471301B discloses a degaussing shielded cable for a subway track system and a preparation method thereof. The degaussing shielded cable comprises a cable core, an insulating sleeve, a shielding sleeve and an outer sheath. The insulating sleeve is coated on the outside of the cable core, the shielding sleeve is coated on the outside of the insulating sleeve, and the outer sheath is coated on the outside of the insulating sleeve. The raw materials of the components of the shielding sleeve include: by weight, 100-110 parts of silicone rubber, 70-80 parts of natural rubber, 3-6 parts of silane coupling agent, 10-15 parts of nickel-plated glass beads, 13-16 parts of triallyl isocyanurate, 8-12 parts of modified carbon nanotubes, 8-10 parts of modified graphene, 2-5 parts of vulcanizing agent, and 8-15 parts of stearic acid. The shielded cable prepared by the present invention has excellent electromagnetic shielding performance, and the components are evenly distributed during the preparation process to avoid the occurrence of agglomeration.
[0004] However, the above invention enhances the electromagnetic shielding effectiveness of the cable by introducing nickel-plated glass beads, modified carbon nanotubes and modified graphene into the shielding layer. However, although the carbon nanotubes and graphene in the above invention can construct a three-dimensional conductive network, both are carbon-based materials and lack synergistic coupling with the nickel-plated glass beads. They cannot enhance broadband shielding through magneto-electric synergy. In addition, the rigidity of the nickel-plated glass beads is too large and they are easily broken when impacted, thereby having a negative impact on the cable structure. Therefore, the shielding performance and impact resistance of the cable prepared by this invention need to be further improved. Summary of the invention
[0005] The object of the present invention is to provide a control cable for signal transmission with high shielding performance, so as to solve the technical problem in the prior art that the shielding performance and impact resistance of the control cable need to be further improved.
[0006] The object of the present invention can be achieved by the following technical solutions: A control cable for signal transmission with high shielding performance, comprising a conductor layer stranded by a plurality of silver-coated copper wires, an insulating layer, a shielding layer, and an outer sheath layer;
[0007] Among them, the insulating layer is obtained by melt-extruding a composite polyvinylidene fluoride material and coating and curing it on the surface of the conductor layer;
[0008] The shielding layer is obtained by wrapping the insulating layer with a flexible shielding foam;
[0009] The outer sheath layer is obtained by melt-extruding a composite polypropylene material and coating and curing it on the surface of the shielding layer.
[0010] Furthermore, the composite polyvinylidene fluoride material comprises the following raw materials by weight: 30-50 parts of polyvinylidene fluoride, 5-10 parts of dioctyl phthalate, 2-5 parts of calcium stearate, 0.5-2 parts of montan wax, 3-10 parts of epoxidized soybean oil, and 0.5-2 parts of polyvinyl alcohol;
[0011] Furthermore, the composite polypropylene material comprises the following raw materials by weight: 70-75 parts of polypropylene, 5-10 parts of dibutyl phthalate, 0.2-1 part of tris(2,4-di-tert-butylphenyl) phosphate, 0.2-2 parts of 2-hydroxy-4-octyloxybenzophenone, 5-10 parts of dioctyl terephthalate, 5-10 parts of calcium carbonate, and 0.5-2 parts of calcium stearate.
[0012] Furthermore, the preparation method of the flexible shielding foam comprises the following steps:
[0013] A1. Add modified nano-particles, cetyltrimethylammonium bromide, sodium hydroxide powder, and deionized water into a reaction kettle, stir at room temperature for 10-15 min, then add polydimethylsiloxane into the reaction kettle, continue to stir for 20-30 min, then add a microsphere foaming agent into the reaction kettle, continue to stir for 20-30 min, and then quickly cool with liquid nitrogen, stand and dry to obtain modified fine powder;
[0014] A2. Add the composite sponge into a mold, fill the sponge voids with the modified fine powder, then hot-press with a hot press for 15-20 min, and release the pressure to obtain the flexible shielding foam.
[0015] The reaction principle for preparing the flexible shielding foam is as follows: Under the catalysis of an alkaline condition, the modified nano-particles and polydimethylsiloxane form a cross-linking in structure. After quickly cooling and drying with liquid nitrogen, the solvent structure forms a low-temperature collapse to obtain the modified fine powder. After the modified fine powder fills the composite sponge, a cross-linking structure is re-formed at high temperature, and the internal microsphere foaming agent expands, and finally the pressure is released to obtain the flexible shielding foam.
[0016] Further, in step A1, the dosage ratio of the modified nano-particles, cetyltrimethylammonium bromide, sodium hydroxide powder, deionized water, polydimethylsiloxane and microsphere foaming agent is 3 - 5 g: 0.3 - 0.4 g: 1 - 2 g: 50 - 60 mL: 20 - 30 g: 2 - 3 g; in step A2, the temperature of the hot press is 100 - 120 °C and the pressure is 10 - 12 MPa.
[0017] Further, the preparation method of the modified nano-particles includes the following steps:
[0018] B1. Transfer the carbonized nano-particles to a tubular furnace, and obtain oxidized nano-particles after oxidation.
[0019] B2. Add the oxidized nano-particles, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and absolute ethanol into a reaction kettle, raise the temperature of the reaction kettle to 40 - 60 °C, keep the temperature for reaction for 2 - 3 h, and obtain the modified nano-particles after post-treatment.
[0020] The reaction principle for preparing the modified nano-particles is as follows: After the carbonized nano-particles are oxidized by the mixed gas under heating conditions, active sites are formed on the surface, thus obtaining oxidized nano-particles. Under the catalysis of an alkaline condition, 3-(2,3-epoxypropoxy)propyltrimethoxysilane undergoes ring-opening to form a structural cross-link with the oxidized nano-particles, and finally the modified nano-particles are prepared.
[0021] Further, in step B1, the preparation method of the oxidized nano-particles is: Transfer the carbonized nano-particles to a tubular furnace, after purging the air with nitrogen, raise the temperature of the reaction kettle to 180 - 200 °C, disconnect the nitrogen, introduce the mixed gas, keep the temperature for reaction for 20 - 30 min, and obtain the oxidized nano-particles after natural cooling to room temperature, wherein the mixed gas is obtained by mixing oxygen and nitrogen in a volume ratio of 4:5 - 6.
[0022] Further, in step B2, the dosage ratio of the oxidized nano-particles, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine and absolute ethanol is 4 - 5 g: 2 - 3 g: 1 - 2 g: 30 - 36 mL. The post-treatment includes: After the reaction is completed, wait for the temperature of the reaction kettle to drop to room temperature, filter the reaction solution by suction to collect the filter cake, wash the filter cake 3 - 5 times with absolute ethanol and deionized water, then transfer the filter cake to a drying oven at 60 °C, and vacuum dry to constant weight to obtain the modified nano-particles.
[0023] Further, the preparation method of the carbonized nano-particles is:
[0024] C1. Add ferric chloride, cobalt chloride and deionized water into a high-pressure reactor. After stirring at room temperature for 10 - 15 min, add a reducing solution into the reactor, seal the high-pressure reactor. During the stirring process, raise the temperature of the reactor to 120 - 160 °C, keep the temperature for reaction for 4 - 6 h, and perform post-treatment to obtain nano-particles;
[0025] C2. Add the nano-particles and deionized water into a high-pressure reactor, raise the temperature of the reactor to 40 - 60 °C, keep the temperature and stir for 10 - 15 min. Add glucose into the high-pressure reactor, continue to stir until the glucose is dissolved, then seal the high-pressure reactor. Raise the temperature of the high-pressure reactor to 140 - 160 °C, keep the temperature for reaction for 4 - 6 h, and perform post-treatment to obtain carbonized nano-particles.
[0026] The reaction principle for preparing the carbonized nano-particles is as follows: at high temperature, hydrazine hydrate in the reducing solution reduces ferric chloride and cobalt chloride under the catalysis of sodium hydroxide, thus obtaining iron-cobalt alloy particles. Under hydrothermal conditions, glucose coats the surface of the iron-cobalt alloy particles and after high-temperature carbonization, carbonized nano-particles are obtained.
[0027] Further, in step C1, the dosage ratio of ferric chloride, cobalt chloride, deionized water and the reducing solution is 3 - 5 g: 2 - 4 g: 30 - 36 mL: 10 - 12 mL. Among them, the reducing solution is prepared from sodium hydroxide and hydrazine hydrate according to the dosage ratio of 1 - 2 g: 10 - 12 mL. The post-treatment includes: after the reaction is completed, wait for the temperature of the reactor to drop to room temperature, filter the reaction solution to collect the filter cake, wash the filter cake with absolute ethanol and deionized water for 3 - 5 times, then transfer the filter cake to a drying oven at 60 °C and vacuum dry to constant weight to obtain nano-particles;
[0028] Further, in step C2, the dosage ratio of the wear-resistant particles, deionized water and glucose is 2 - 3 g: 30 - 36 mL: 8 - 10 g. The post-treatment includes: after the reaction is completed, wait for the temperature of the reactor to drop to room temperature, filter the reaction solution to collect the filter cake, wash the filter cake with absolute ethanol and deionized water for 3 - 5 times, then transfer the filter cake to a drying oven at 60 °C and vacuum dry to constant weight. Then add it into a tubular furnace. After the tubular furnace is purged with nitrogen, heat it up to 400 - 420 °C at a heating rate of 3 - 5 °C / min and keep the temperature for reaction for 3 - 4 h to obtain carbonized nano-particles.
[0029] Further, the preparation method of the composite sponge includes the following steps:
[0030] D1. Add nickel nitrate hexahydrate, copper chloride dihydrate, tetraethyl orthosilicate, 2,4-pentanedione and ethanol into a reactor, stir at room temperature for 4 - 6 h to obtain a precursor solution;
[0031] D2. The precursor solution is spun using air-jet spinning and collected using a cage-shaped collector to obtain a composite sponge precursor, which is then post-treated to obtain the composite sponge.
[0032] The reaction principle for preparing the composite sponge is as follows: during stirring, 2,4-pentanedione, nickel nitrate, and iron chloride form a complex structure, and tetraethyl orthosilicate forms a structural supplement. After stirring, the precursor solution is obtained. The solvent of the precursor solution volatilizes under air-jet spinning, and after being collected by the cage-shaped collector, a composite sponge precursor is obtained. After high-temperature crystal transformation, the composite sponge is obtained.
[0033] Furthermore, in step D1, the dosage ratio of nickel nitrate hexahydrate, copper chloride dihydrate, tetraethyl orthosilicate, 2,4-pentanedione, and ethanol is 2 - 3 g : 3 - 4 g : 5 - 6 g : 1 - 2 g : 20 - 24 mL;
[0034] Furthermore, in step D2, the air-jet spinning operation is as follows: the precursor solution is loaded into a syringe and extruded at a rate of 1 - 2 mL / h. The high-speed air flow rate is 10 - 12 m / s, and the distance between the cage-shaped collector and the syringe needle tip is 30 - 50 cm. The post-treatment includes: transferring the composite sponge precursor to a tube furnace, introducing nitrogen for protection. The tube heating furnace is heated to 800 - 1000 °C at a rate of 8 - 10 °C / min, held for 5 - 6 h, then naturally cooled to 300 - 600 °C, after which the nitrogen is disconnected, and water vapor is introduced at a rate of 80 - 100 sccm, held for 2 - 3 h, and then naturally cooled to obtain the composite sponge.
[0035] Furthermore, the preparation method of the control cable includes the following steps:
[0036] S1. A number of silver-coated copper wires are stranded to obtain a conductor layer;
[0037] S2. The composite polyvinylidene fluoride material is added to a twin-screw extruder and melt-extruded to coat the surface of the conductor layer. After natural cooling and curing, an insulating layer is obtained;
[0038] S3. The flexible shielding foam is wrapped around the insulating layer to obtain a shielding layer;
[0039] S4. The composite polypropylene is added to a twin-screw extruder and melt-extruded to coat the surface of the shielding layer. After natural cooling and curing, an outer sheath layer is obtained, thus obtaining the control cable.
[0040] Furthermore, in step S2, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port are 240 °C, 245 °C, 245 °C, 260 °C, 260 °C, 270 °C, 270 °C, and 280 °C in sequence. The main machine speed of the twin-screw extruder is 80 - 120 rpm, and the pressure is 100 - 150 bar;
[0041] Further, in step S4, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port towards the discharge port are 210°C, 215°C, 215°C, 220°C, 220°C, 230°C, 230°C, and 240°C in sequence. The main machine speed of the twin-screw extruder is 80 - 120 rpm, and the pressure is 100 - 150 bar.
[0042] The present invention has the following beneficial effects:
[0043] 1. The present invention improves the electromagnetic shielding performance from multiple aspects through material structure optimization and component synergy. First, the material combines iron-cobalt alloy and nickel-cobalt-silicon fiber. The magnetic part absorbs low-frequency electromagnetic waves, and the conductive part reflects high-frequency electromagnetic waves. The two cooperate to cover a wider frequency range. Second, the silicon-oxygen groups modified after the surface oxidation of the carbon layer help the material disperse more evenly in the polymer, forming a continuous conductive network and enhancing the overall shielding effect. At the same time, the porous structure inside the material extends the propagation path of electromagnetic waves through multiple reflections and scatterings, enabling more energy to be gradually consumed. Moreover, the magnetic difference between the nickel-cobalt alloy and the iron-cobalt component generates complementary magnetic losses in the electromagnetic field, further improving the energy absorption efficiency. The combination of the fiber and the sponge matrix not only maintains the flexibility of the material but also enhances the reflection and absorption of electromagnetic waves through the staggered conductive paths. These designs achieve the efficient shielding of electromagnetic waves through the mutual complementarity of different material properties and the synergy of the structure, and are applicable to scenarios with complex material property requirements such as flexible cables.
[0044] 2. The present invention also synergistically improves the impact resistance and tensile strength of the cable through structural design and material cooperation. First, the carbon layer and silicon-oxygen groups on the surface of the iron-cobalt alloy form structural layers with different hardnesses: the internal alloy bears the external force, the middle carbon layer disperses the pressure, and the outer flexible matrix buffers the impact through elastic deformation, reducing the risk of internal cracking of the material. Second, the fibers in the composite sponge form a network skeleton to provide tensile support. The microporous structure absorbs energy through compression deformation when impacted. The outer dense structure resists the initial impact, and the inner loose structure further slows down the impact transmission, enabling the layered design of the material to gradually disperse the impact force from the outside to the inside and avoid local overload. These designs comprehensively improve the impact resistance, tensile strength, and flexibility of the material through the mutual complementarity of different material properties, the coordination of structural levels, and the synergy of energy absorption methods. Description of the Drawings
[0045] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the following drawings are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.
[0046] Figure 1 Schematic three-dimensional structure diagram of the control cable prepared according to the present invention.
[0047] In the figure: 1, conductor layer; 2, insulating layer; 3, shielding layer; 4, outer sheath layer. Specific embodiments
[0048] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0049] The polyvinyl alcohol used in the present invention is purchased from Anhui Wanhui Group Co., Ltd., and the product name is 05-99(L);
[0050] The microsphere foaming agent used in the present invention is purchased from Beijing Yijin Technology Co., Ltd., and the product number is UNICELL;
[0051] The polydimethylsiloxane used in the present invention is purchased from Shanghai Titan Technology Co., Ltd., and the product number is 89315E.
[0052] Example 1
[0053] This example provides a method for preparing carbonized nanoparticles for use in the preparation of a control cable for signal transmission with high shielding performance, including the following steps:
[0054] Step I. Preparation of nanoparticles
[0055] Weigh: 10.0 g of sodium hydroxide and 100.0 mL of hydrazine hydrate to prepare a reducing solution;
[0056] Weigh: 30.0 g of ferric chloride, 20.0 g of cobalt chloride and 300.0 mL of deionized water and add them to a high-pressure reaction kettle. After stirring at room temperature for 10 min, add 100.0 mL of the reducing solution to the reaction kettle, seal the high-pressure reaction kettle, and during the stirring process, the temperature of the reaction kettle is raised to 120 °C, keep the temperature for reaction for 4 h. After the reaction is completed, wait for the temperature of the reaction kettle to drop to room temperature, filter the reaction solution to collect the filter cake, wash the filter cake 3 times with absolute ethanol and deionized water, and then transfer the filter cake to a drying oven at 60 °C and vacuum dry to constant weight to obtain the nanoparticles.
[0057] Step II. Preparation of carbonized nanoparticles
[0058] Preparation: 200.0 g of nanoparticles and 300.0 mL of deionized water were added to a high-pressure reactor. The temperature of the reactor was raised to 40 °C, and it was kept warm and stirred for 10 min. 80.0 g of glucose was added to the high-pressure reactor. After continuing to stir until the glucose was dissolved, the high-pressure reactor was sealed. Then, the temperature of the high-pressure reactor was raised to 140 °C, and it was kept warm and reacted for 4 h. After the reaction was completed, when the temperature of the reactor dropped to room temperature, the reaction solution was filtered by suction to collect the filter cake. After washing the filter cake 3 times with absolute ethanol and deionized water, the filter cake was transferred to a drying oven at 60 °C and vacuum dried to a constant weight. Then, it was added to a tube furnace. After the tube furnace was purged with nitrogen, it was heated to 400 °C at a heating rate of 3 °C / min and kept warm and reacted for 3 h to obtain carbonized nanoparticles.
[0059] Example 2
[0060] This example provides a preparation method of carbonized nanoparticles for a control cable used for signal transmission with high shielding performance, including the following steps:
[0061] Step I. Preparation of nanoparticles
[0062] Weigh: 20.0 g of sodium hydroxide and 120.0 mL of hydrazine hydrate were prepared to obtain a reducing solution.
[0063] Weigh: 50.0 g of ferric chloride, 40.0 g of cobalt chloride and 360.0 mL of deionized water were added to a high-pressure reactor. After stirring at room temperature for 10 min, 120.0 mL of the reducing solution was added to the reactor. Then, the high-pressure reactor was sealed. During the stirring process, the temperature of the reactor was raised to 160 °C and kept warm and reacted for 6 h. After the reaction was completed, when the temperature of the reactor dropped to room temperature, the reaction solution was filtered by suction to collect the filter cake. After washing the filter cake 5 times with absolute ethanol and deionized water, the filter cake was transferred to a drying oven at 60 °C and vacuum dried to a constant weight to obtain nanoparticles.
[0064] Step II. Preparation of carbonized nanoparticles
[0065] Preparation: 30.0 g of nanoparticles and 360.0 mL of deionized water were added to a high-pressure reactor. The temperature of the reactor was raised to 60 °C, and it was kept warm and stirred for 15 min. 100.0 g of glucose was added to the high-pressure reactor. After continuing to stir until the glucose was dissolved, the high-pressure reactor was sealed. Then, the temperature of the high-pressure reactor was raised to 160 °C and kept warm and reacted for 6 h. After the reaction was completed, when the temperature of the reactor dropped to room temperature, the reaction solution was filtered by suction to collect the filter cake. After washing the filter cake 5 times with absolute ethanol and deionized water, the filter cake was transferred to a drying oven at 60 °C and vacuum dried to a constant weight. Then, it was added to a tube furnace. After the tube furnace was purged with nitrogen, it was heated to 420 °C at a heating rate of 5 °C / min and kept warm and reacted for 4 h to obtain carbonized nanoparticles.
[0066] Example 3
[0067] This embodiment provides a preparation method of carbonized nanoparticles for preparing a control cable for signal transmission with high shielding performance, including the following steps:
[0068] Step Ⅰ. Preparation of nanoparticles
[0069] Weigh: 15.0 g of sodium hydroxide and 120.0 mL of hydrazine hydrate to prepare a reducing solution;
[0070] Weigh: 40.0 g of ferric chloride, 30.0 g of cobalt chloride and 320.0 mL of deionized water and add them to a high-pressure reactor. After stirring at room temperature for 12 min, add 120.0 mL of the reducing solution to the reactor, seal the high-pressure reactor, and during the stirring process, raise the temperature of the reactor to 160 °C, keep the temperature for reaction for 5 h. After the reaction is completed, wait for the temperature of the reactor to drop to room temperature, filter the reaction solution to collect the filter cake, wash the filter cake 4 times with absolute ethanol and deionized water, then transfer the filter cake to a drying oven at 60 °C and vacuum dry to constant weight to obtain nanoparticles.
[0071] Step Ⅱ. Preparation of carbonized nanoparticles
[0072] Prepare: Add 270.0 g of nanoparticles and 320.0 mL of deionized water to a high-pressure reactor, raise the temperature of the reactor to 50 °C, keep the temperature and stir for 12 min, add 90.0 g of glucose to the high-pressure reactor, continue to stir until the glucose is dissolved, then seal the high-pressure reactor, raise the temperature of the high-pressure reactor to 150 °C, keep the temperature for reaction for 5 h. After the reaction is completed, wait for the temperature of the reactor to drop to room temperature, filter the reaction solution to collect the filter cake, wash the filter cake 4 times with absolute ethanol and deionized water, then transfer the filter cake to a drying oven at 60 °C and vacuum dry to constant weight. After that, add it to a tubular furnace. After the tubular furnace is purged with nitrogen, heat it up to 420 °C at a heating rate of 4 °C / min and keep the temperature for reaction for 4 h to obtain carbonized nanoparticles.
[0073] Example 4
[0074] This embodiment provides a preparation method of modified nanoparticles for preparing a control cable for signal transmission with high shielding performance, including the following steps:
[0075] Step ⑴. Preparation of oxidized nanoparticles
[0076] Weigh: Transfer 100.0 g of the carbonized nanoparticles prepared in Example 1 to a tubular furnace. After purging the air with nitrogen, raise the temperature of the reactor to 180 °C, disconnect the nitrogen, and introduce a mixed gas obtained by mixing oxygen and nitrogen in a volume ratio of 4:5. Keep the temperature for reaction for 20 min, and then naturally cool to room temperature to obtain oxidized nanoparticles.
[0077] Step ⑵. Preparation of modified nanoparticles
[0078] Weigh: 40.0 g of nano-oxide particles, 20.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 10.0 g of triethylamine and 300.0 mL of absolute ethanol were added to a reaction kettle. The temperature of the reaction kettle was raised to 40 °C and kept for reaction for 2 h. After the reaction was completed, after the temperature of the reaction kettle was lowered to room temperature, the reaction solution was filtered to collect the filter cake. After washing the filter cake 3 times with absolute ethanol and deionized water, the filter cake was transferred to a drying oven at 60 °C and vacuum dried to constant weight to obtain modified nano-particles.
[0079] Example 5
[0080] This example provides a method for preparing modified nano-particles for use in the preparation of a control cable for signal transmission with high shielding performance, including the following steps:
[0081] Step (1), preparing nano-oxide particles
[0082] Weigh: 100.0 g of the carbonized nano-particles prepared in Example 2 were transferred to a tubular furnace. After purging the air with nitrogen, the temperature of the reaction kettle was raised to 200 °C. After disconnecting the nitrogen, a mixed gas obtained by mixing oxygen and nitrogen in a volume ratio of 4:6 was introduced, and the reaction was kept for 30 min. After naturally cooling to room temperature, nano-oxide particles were obtained.
[0083] Step (2), preparing modified nano-particles
[0084] Weigh: 50.0 g of nano-oxide particles, 30.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 20.0 g of triethylamine and 360.0 mL of absolute ethanol were added to a reaction kettle. The temperature of the reaction kettle was raised to 60 °C and kept for reaction for 3 h. After the reaction was completed, after the temperature of the reaction kettle was lowered to room temperature, the reaction solution was filtered to collect the filter cake. After washing the filter cake 5 times with absolute ethanol and deionized water, the filter cake was transferred to a drying oven at 60 °C and vacuum dried to constant weight to obtain modified nano-particles.
[0085] Example 6
[0086] This example provides a method for preparing modified nano-particles for use in the preparation of a control cable for signal transmission with high shielding performance, including the following steps:
[0087] Step (1), preparing nano-oxide particles
[0088] Weigh: 100.0 g of the carbonized nano-particles prepared in Example 3 were transferred to a tubular furnace. After purging the air with nitrogen, the temperature of the reaction kettle was raised to 200 °C. After disconnecting the nitrogen, a mixed gas obtained by mixing oxygen and nitrogen in a volume ratio of 4:5 was introduced, and the reaction was kept for 25 min. After naturally cooling to room temperature, nano-oxide particles were obtained.
[0089] Step ⑵, preparing modified nanoparticles
[0090] Weigh: 48.0 g of nano-oxide particles, 24.0 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 16.0 g of triethylamine and 320.0 mL of absolute ethanol and add them to a reaction kettle. Raise the temperature of the reaction kettle to 50 °C and keep the temperature for 3 h. After the reaction is completed, wait for the temperature of the reaction kettle to drop to room temperature, then filter the reaction solution to collect the filter cake. Wash the filter cake 4 times with absolute ethanol and deionized water, and then transfer the filter cake to a drying oven at 60 °C and vacuum dry it to constant weight to obtain modified nanoparticles.
[0091] Example 7
[0092] This example provides a preparation method of a composite sponge for preparing a control cable for signal transmission with high shielding performance, including the following steps:
[0093] Step ①, preparing a precursor solution
[0094] Weigh: 20.0 g of nickel nitrate hexahydrate, 30.0 g of copper chloride dihydrate, 50.0 g of tetraethyl orthosilicate, 10.0 g of 2,4-pentanedione and 200.0 mL of ethanol and add them to a reaction kettle. Stir at room temperature for 4 h to obtain a precursor solution.
[0095] Step ②, preparing a composite sponge
[0096] Weigh: 200.0 mL of the precursor solution and load it into a syringe. Extrude it at a rate of 1 mL / h, with a high-speed air flow rate of 10 m / s and the distance between the cage-shaped collector and the syringe needle tip being 30 cm. After collecting with the cage-shaped collector, obtain a composite sponge precursor. Transfer the composite sponge precursor to a tubular furnace, introduce nitrogen for protection, and heat the tubular furnace to 800 °C at a rate of 8 °C / min, then keep the temperature for 5 h, and then naturally cool to 300 °C. Disconnect the nitrogen and introduce water vapor at a rate of 80 sccm, keep the temperature for 2 h, and then naturally cool to obtain a composite sponge.
[0097] Example 8
[0098] This example provides a preparation method of a composite sponge for preparing a control cable for signal transmission with high shielding performance, including the following steps:
[0099] Step ①, preparing a precursor solution
[0100] Weigh: 30.0 g of nickel nitrate hexahydrate, 40.0 g of copper chloride dihydrate, 60.0 g of tetraethyl orthosilicate, 20.0 g of 2,4-pentanedione and 240.0 mL of ethanol and add them to a reaction kettle. Stir at room temperature for 6 h to obtain a precursor solution.
[0101] Step ②, preparing a composite sponge
[0102] Weighing: 200.0 mL of the precursor solution was filled into a syringe and extruded at a rate of 2 mL / h. The high-speed gas flow rate was 12 m / s, and the distance between the cage collector and the syringe needle tip was 50 cm. After collecting with the cage collector, a composite sponge precursor was obtained. The composite sponge precursor was transferred to a tubular furnace, and nitrogen was introduced for protection. The tubular heating furnace was heated to 1000 °C at a rate of 10 °C / min, held for 6 h, then naturally cooled to 600 °C, the nitrogen was disconnected, and steam was introduced at a rate of 100 sccm. After holding for 3 h, it was naturally cooled to obtain the composite sponge.
[0103] Example 9
[0104] This example provides a method for preparing a composite sponge for use in the preparation of a control cable for signal transmission with high shielding performance, including the following steps:
[0105] Step ①, preparing the precursor solution
[0106] Weighing: 24.0 g of nickel nitrate hexahydrate, 36.0 g of copper chloride dihydrate, 54.0 g of tetraethyl orthosilicate, 15.0 g of 2,4-pentanedione, and 210.0 mL of ethanol were added to a reaction kettle and stirred at room temperature for 5 h to obtain the precursor solution.
[0107] Step ②, preparing the composite sponge
[0108] Weighing: 200.0 mL of the precursor solution was filled into a syringe and extruded at a rate of 1.6 mL / h. The high-speed gas flow rate was 12 m / s, and the distance between the cage collector and the syringe needle tip was 40 cm. After collecting with the cage collector, a composite sponge precursor was obtained. The composite sponge precursor was transferred to a tubular furnace, and nitrogen was introduced for protection. The tubular heating furnace was heated to 900 °C at a rate of 9 °C / min, held for 5 h, then naturally cooled to 500 °C, the nitrogen was disconnected, and steam was introduced at a rate of 100 sccm. After holding for 3 h, it was naturally cooled to obtain the composite sponge.
[0109] Example 10
[0110] This example provides a method for preparing a flexible shielding foam for use in the preparation of a control cable for signal transmission with high shielding performance, including the following steps:
[0111] Step ㈠, preparing the modified micropowder
[0112] Weigh: 30.0 g of the modified nanoparticles prepared in Example 4, 3.0 g of cetyltrimethylammonium bromide, 10.0 g of sodium hydroxide powder, and 500.0 mL of deionized water were added to a reaction kettle. After stirring at room temperature for 10 min, 200.0 g of polydimethylsiloxane was added to the reaction kettle. After continuing to stir for 20 min, 20.0 g of microsphere foaming agent was added to the reaction kettle. After continuing to stir for 20 min, it was rapidly cooled with liquid nitrogen. After standing and drying, modified fine powder was obtained.
[0113] Step (ii), preparing flexible shielding foam
[0114] Weigh: The composite sponge prepared in Example 7 was added to a mold. After filling the sponge voids with the modified fine powder, it was hot-pressed using a hot press. The temperature of the hot press was 100 °C, the pressure was 10 MPa. After hot-pressing for 15 min, the pressure was released to obtain flexible shielding foam.
[0115] Example 11
[0116] This example provides a preparation method of modified nanoparticles for preparing a control cable for signal transmission with high shielding performance, including the following steps:
[0117] Step (i), preparing modified fine powder
[0118] Weigh: 50.0 g of the modified nanoparticles prepared in Example 5, 4.0 g of cetyltrimethylammonium bromide, 20.0 g of sodium hydroxide powder, and 600.0 mL of deionized water were added to a reaction kettle. After stirring at room temperature for 15 min, 300.0 g of polydimethylsiloxane was added to the reaction kettle. After continuing to stir for 30 min, 30.0 g of microsphere foaming agent was added to the reaction kettle. After continuing to stir for 30 min, it was rapidly cooled with liquid nitrogen. After standing and drying, modified fine powder was obtained.
[0119] Step (ii), preparing flexible shielding foam
[0120] Weigh: The composite sponge prepared in Example 8 was added to a mold. After filling the sponge voids with the modified fine powder, it was hot-pressed using a hot press. The temperature of the hot press was 120 °C, the pressure was 12 MPa. After hot-pressing for 20 min, the pressure was released to obtain flexible shielding foam.
[0121] Example 12
[0122] This example provides a preparation method of modified nanoparticles for preparing a control cable for signal transmission with high shielding performance, including the following steps:
[0123] Step (i), preparing modified fine powder
[0124] Weigh: 40.0 g of the modified nanoparticles prepared in Example 6, 3.6 g of cetyltrimethylammonium bromide, 16.0 g of sodium hydroxide powder and 540.0 mL of deionized water were added to a reaction kettle. After stirring at room temperature for 12 min, 240.0 g of polydimethylsiloxane was added to the reaction kettle. After continuing to stir for 25 min, 25.0 g of microsphere foaming agent was added to the reaction kettle. After continuing to stir for 25 min, it was rapidly cooled with liquid nitrogen and dried by standing to obtain modified fine powder.
[0125] Step (ii), preparing flexible shielding foam
[0126] Weigh: The composite sponge prepared in Example 9 was added to a mold. After filling the sponge voids with the modified fine powder, it was hot-pressed using a hot press. The temperature of the hot press was 120 °C, the pressure was 12 MPa, and after hot-pressing for 18 min, the pressure was released to obtain flexible shielding foam.
[0127] Example 13
[0128] This example provides a preparation method of a control cable for signal transmission with high shielding performance, including the following steps:
[0129] Step one, preparing a conductor layer
[0130] Seven silver-coated copper wires were stranded to obtain conductor layer 1.
[0131] Step two, preparing an insulating layer
[0132] Weigh: 30 parts of polyvinylidene fluoride, 5 parts of dioctyl phthalate, 2 parts of calcium stearate, 0.5 part of montan wax, 3 parts of epoxidized soybean oil and 0.5 part of polyvinyl alcohol were added to a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port were 240 °C, 245 °C, 245 °C, 260 °C, 260 °C, 270 °C, 270 °C, 280 °C in sequence. The main motor speed of the twin-screw extruder was 80 rpm, the pressure was 100 bar, and it was melt-extruded and coated on the surface of the conductor layer. After natural cooling and curing, insulating layer 2 was obtained;
[0133] Step three, preparing a shielding layer
[0134] The flexible shielding foam prepared in Example 10 was wrapped around insulating layer 2 to obtain shielding layer 3.
[0135] Step four, preparing a control cable
[0136] Weigh: 70 parts of polypropylene, 5 parts of dibutyl phthalate, 0.2 parts of tris(2,4-di-tert-butylphenyl) phosphate, 0.2 parts of 2-hydroxy-4-octyloxybenzophenone, 5 parts of dioctyl terephthalate, 5 parts of calcium carbonate and 0.5 parts of calcium stearate and add them to a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed inlet to the discharge outlet are 210 °C, 215 °C, 215 °C, 220 °C, 220 °C, 230 °C, 230 °C, and 240 °C in sequence. The main motor speed of the twin-screw extruder is 80 rpm and the pressure is 100 bar. After melting and extruding and coating on the surface of the shielding layer and naturally cooling and solidifying, the outer sheath layer 4 is obtained, that is, the control cable is obtained.
[0137] Example 14
[0138] This example provides a method for preparing a control cable for signal transmission with high shielding performance, including the following steps:
[0139] Step 1: Prepare the conductor layer
[0140] Strand 7 silver-coated copper wires to obtain the conductor layer 1.
[0141] Step 2: Prepare the insulation layer
[0142] Weigh: 50 parts of polyvinylidene fluoride, 10 parts of dioctyl phthalate, 5 parts of calcium stearate, 2 parts of montan wax, 10 parts of epoxidized soybean oil and 2 parts of polyvinyl alcohol and add them to a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed inlet to the discharge outlet are 240 °C, 245 °C, 245 °C, 260 °C, 260 °C, 270 °C, 270 °C, and 280 °C in sequence. The main motor speed of the twin-screw extruder is 120 rpm and the pressure is 150 bar. After melting and extruding and coating on the surface of the conductor layer and naturally cooling and solidifying, the insulation layer 2 is obtained;
[0143] Step 3: Prepare the shielding layer
[0144] Wrap the flexible shielding foam prepared in Example 11 around the insulation layer 2 to obtain the shielding layer 3.
[0145] Step 4: Prepare the control cable
[0146] Weigh and add: 75 parts of polypropylene, 10 parts of dibutyl phthalate, 1 part of tris(2,4-di-tert-butylphenyl) phosphate, 2 parts of 2-hydroxy-4-octyloxybenzophenone, 10 parts of dioctyl terephthalate, 10 parts of calcium carbonate and 2 parts of calcium stearate into a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed inlet to the discharge outlet are 210°C, 215°C, 215°C, 220°C, 220°C, 230°C, 230°C, 240°C in sequence. The main motor speed of the twin-screw extruder is 120 rpm, and the pressure is 150 bar. Melt and extrude to coat the surface of the shielding layer, and after natural cooling and solidification, the outer sheath layer 4 is obtained, that is, the control cable is obtained.
[0147] Example 15
[0148] This example provides a method for preparing a control cable for signal transmission with high shielding performance, including the following steps:
[0149] Step 1: Prepare the conductor layer
[0150] Strand 7 silver-coated copper wires to obtain the conductor layer 1.
[0151] Step 2: Prepare the insulating layer
[0152] Weigh and add: 40 parts of polyvinylidene fluoride, 8 parts of dioctyl phthalate, 3 parts of calcium stearate, 1 part of montan wax, 5 parts of epoxidized soybean oil and 1 part of polyvinyl alcohol into a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed inlet to the discharge outlet are 240°C, 245°C, 245°C, 260°C, 260°C, 270°C, 270°C, 280°C in sequence. The main motor speed of the twin-screw extruder is 100 rpm, and the pressure is 120 bar. Melt and extrude to coat the surface of the conductor layer, and after natural cooling and solidification, the insulating layer 2 is obtained;
[0153] Step 3: Prepare the shielding layer
[0154] Wrap the flexible shielding foam prepared in Example 12 around the insulating layer 2 to obtain the shielding layer 3.
[0155] Step 4: Prepare the control cable
[0156] Weigh: 72 parts of polypropylene, 8 parts of dibutyl phthalate, 0.5 part of tris(2,4-di-tert-butylphenyl) phosphate, 1 part of 2-hydroxy-4-octyloxybenzophenone, 8 parts of dioctyl terephthalate, 8 parts of calcium carbonate and 1 part of calcium stearate are added to a twin-screw extruder. The temperatures of the eight temperature zones of the twin-screw extruder from the feed port to the discharge port are 210 °C, 215 °C, 215 °C, 220 °C, 220 °C, 230 °C, 230 °C, and 240 °C in sequence. The main machine speed of the twin-screw extruder is 100 rpm, and the pressure is 120 bar. It is melt-extruded and coated on the surface of the shielding layer. After natural cooling and curing, the outer sheath layer 4 is obtained, that is, the control cable is obtained.
[0157] Comparative Example 1
[0158] The difference between this comparative example and Example 15 is that in the preparation of the flexible shielding foam used, the use of modified nano-particles is cancelled, and the carbonized nano-particles used in the preparation process of the modified nano-particles are used to replace the modified nano-particles in equal amounts.
[0159] Comparative Example 2
[0160] The difference between this comparative example and Example 15 is that in the preparation of the flexible shielding foam used, tetraethyl orthosilicate is cancelled in the preparation of the composite sponge used in step (ii).
[0161] Comparative Example 3
[0162] The difference between this comparative example and Example 15 is that in the preparation of the flexible shielding foam used, the use of the composite sponge is cancelled.
[0163] Performance test:
[0164] Refer to the standard GB / T 19666-2019 "General Technical Requirements for Electromagnetic Shielding Films" to test the anti-electromagnetic interference level of the control cables prepared in Examples 13-15 and Comparative Examples 1-3;
[0165] Refer to the standard GB / T 1843-2008 "Determination of Izod Impact Strength of Plastics" to test the Izod impact strength of the control cables prepared in Examples 13-15 and Comparative Examples 1-3;
[0166] Refer to the standard GB / T 17737.314-2018 "Coaxial Communication Cables - Part 1-314: Mechanical Test Methods - Bending Test of Cables" to conduct a cyclic bending test on the control cables prepared in Examples 13-15 and Comparative Examples 1-3, record the number of recyclable times, and determine the flexibility of the flexible coaxial cable;
[0167] The tensile strength of the control cables prepared in Examples 13-15 and Comparative Examples 1-3 was measured with reference to the standard GB / T 17737.316-2018 "Coaxial communication cables - Part 1-316: Mechanical test methods - Maximum tensile force test of cables"; the specific data are shown in Table 1.
[0168] Table 1 - Performance test data table of each specimen
[0169]
[0170]
[0171] Data analysis:
[0172] By comparing and analyzing the data in Table 1 above, it can be found that the control cable prepared by the present invention has an electromagnetic interference resistance level of SE-1, a cantilever beam impact strength of 49.6 MPa, a cycle number of 3.55 million times, and a tensile strength of 66.8 MPa, and all data are superior to those of the comparative examples;
[0173] It shows that the present invention improves the electromagnetic shielding performance from multiple aspects through material structure optimization and component synergy. First, the material combines iron-cobalt alloy and nickel-cobalt-silicon fiber. The magnetic part absorbs low-frequency electromagnetic waves, and the conductive part reflects high-frequency electromagnetic waves. The two cooperate to cover a wider frequency range. Second, the silicon-oxygen groups modified after the surface oxidation of the carbon layer help the material disperse more evenly in the polymer, forming a continuous conductive network and enhancing the overall shielding effect; at the same time, the porous structure inside the material extends the propagation path of electromagnetic waves through multiple reflections and scatterings, enabling more energy to be gradually consumed, and the magnetic difference between the nickel-cobalt alloy and the iron-cobalt component generates complementary magnetic losses in the electromagnetic field, further improving the energy absorption efficiency; the combination of the fiber and the sponge matrix not only maintains the flexibility of the material but also enhances the reflection and absorption of electromagnetic waves through the staggered conductive paths. These designs achieve the efficient shielding of electromagnetic waves through the mutual complementarity of different material properties and the synergy in structure, and are applicable to scenarios with complex material property requirements such as flexible cables.
[0174] It should be noted that in the present invention, through structural design and material combination, the impact resistance and tensile properties of the cable can be synergistically improved in multiple aspects. First, the carbon layer and silicon-oxygen groups on the surface of the iron-cobalt alloy form structural layers with different hardnesses: the internal alloy bears the external force, the middle carbon layer disperses the pressure, and the outer flexible matrix buffers the impact through elastic deformation, reducing the risk of internal cracking of the material. Second, the fibers in the composite sponge form a network skeleton to provide tensile support, and the microporous structure absorbs energy through compressive deformation when impacted. The outer dense structure resists the initial impact, and the inner loose structure further slows down the impact transmission, enabling the layered design of the material to gradually disperse the impact force from the outside to the inside, avoiding local overload. These designs comprehensively improve the impact resistance, tensile properties, and flexibility of the material through the complementarity of different material properties, the coordination of structural levels, and the synergy of energy absorption methods.
[0175] The above content is only an example and explanation of the structure of the present invention. Those skilled in the art of this technology can make various modifications or supplements to the described specific embodiments or use similar methods for substitution, as long as they do not deviate from the structure of the invention or exceed the scope defined by this claim book, they should fall within the protection scope of the present invention.
[0176] In the description of this specification, the description with reference to terms such as "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.
[0177] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not elaborate on all the details, nor do they limit the invention to only the specific implementation manners. Obviously, according to the content of this specification, many modifications and changes can be made. This specification selects and specifically describes these embodiments to better explain the principle and practical application of the present invention, so that those skilled in the art of this technology can well understand and utilize the present invention. The present invention is only limited by the claim book and its full scope and equivalents.
Claims
1. A control cable for signal transmission with high shielding performance, characterized in that, It includes a conductor layer (1) composed of several silver-coated copper wires twisted together, an insulating layer (2), a shielding layer (3), and an outer sheath layer (4); Among them, the insulating layer (2) is obtained by melt-extruding a composite polyvinylidene fluoride material and coating and curing it on the surface of the conductor layer (1); The shielding layer (3) is obtained by wrapping the insulating layer (2) with a flexible shielding foam; The outer sheath layer (4) is obtained by melt-extruding a composite polypropylene material and coating and curing it on the surface of the shielding layer (3).
2. The control cable for signal transmission with high shielding performance according to claim 1, characterized in that, The preparation method of the flexible shielding foam includes the following steps: A1. Add modified nano-particles, cetyltrimethylammonium bromide, sodium hydroxide powder, and deionized water into a reaction kettle. After stirring at room temperature for 10 - 15 min, add polydimethylsiloxane into the reaction kettle. After continuing to stir for 20 - 30 min, add a microsphere foaming agent into the reaction kettle. After continuing to stir for 20 - 30 min, rapidly cool with liquid nitrogen. After standing and drying, modified micro-powder is obtained; A2. Add the composite sponge into a mold. After filling the sponge voids with the modified micro-powder, hot-press with a hot press for 15 - 20 min, and then release the pressure to obtain the flexible shielding foam.
3. A control cable for signal transmission with high shielding performance according to claim 2, characterized in that, In step A1, the dosage ratio of the modified nano-particles, cetyltrimethylammonium bromide, sodium hydroxide powder, deionized water, polydimethylsiloxane, and the microsphere foaming agent is 3 - 5 g: 0.3 - 0.4 g: 1 - 2 g: 50 - 60 mL: 20 - 30 g: 2 - 3 g; in step A2, the temperature of the hot press is 100 - 120 °C, and the pressure is 10 - 12 MPa.
4. A control cable for signal transmission with high shielding performance according to claim 2, characterized in that The preparation method of the modified nano-particles includes the following steps: B1. Transfer the carbonized nano-particles to a tubular furnace, and obtain oxidized nano-particles after oxidation; B2. Add the oxidized nano-particles, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine, and absolute ethanol into a reaction kettle. Raise the temperature of the reaction kettle to 40 - 60 °C, keep the temperature for reaction for 2 - 3 h, and perform post-treatment to obtain the modified nano-particles.
5. A control cable for signal transmission with high shielding performance according to claim 4, characterized in that, In step B1, the preparation method of the oxidized nano-particles is: transfer the carbonized nano-particles to a tubular furnace. After purging the air with nitrogen, raise the temperature of the reaction kettle to 180 - 200 °C, disconnect the nitrogen, and introduce a mixed gas. Keep the temperature for reaction for 20 - 30 min, and naturally cool to room temperature to obtain the oxidized nano-particles. Among them, the mixed gas is obtained by mixing oxygen and nitrogen according to a volume ratio of 4:5 - 6; in step B2, the dosage ratio of the oxidized nano-particles, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, triethylamine, and absolute ethanol is 4 - 5 g: 2 - 3 g: 1 - 2 g: 30 - 36 mL.
6. A control cable for signal transmission with high shielding performance according to claim 4, characterized in that, The preparation method of the carbonized nano-particles is: C1. Add ferric chloride, cobalt chloride, and deionized water into a high-pressure reaction kettle. After stirring at room temperature for 10 - 15 min, add a reducing solution into the reaction kettle, seal the high-pressure reaction kettle. During the stirring process, raise the temperature of the reaction kettle to 120 - 160 °C, keep the temperature for reaction for 4 - 6 h, and perform post-treatment to obtain nano-particles; C2. Add the nanoparticles and deionized water into a high-pressure reactor. Raise the temperature of the reactor to 40 - 60 °C, keep warm and stir for 10 - 15 min. Add glucose into the high-pressure reactor, continue stirring until the glucose is dissolved. After sealing the high-pressure reactor, raise the temperature of the high-pressure reactor to 140 - 160 °C, keep warm and react for 4 - 6 h, and perform post-treatment to obtain carbonized nanoparticles.
7. A control cable for signal transmission with high shielding performance according to claim 6, characterized in that, In step C1, the dosage ratio of ferric chloride, cobalt chloride, deionized water and the reducing solution is 3 - 5 g: 2 - 4 g: 30 - 36 mL: 10 - 12 mL. Among them, the reducing solution is prepared from sodium hydroxide and hydrazine hydrate according to the dosage ratio of 1 - 2 g: 10 - 12 mL; in step C2, the dosage ratio of the wear-resistant particles, deionized water and glucose is 2 - 3 g: 30 - 36 mL: 8 - 10 g.
8. A control cable for signal transmission with high shielding performance according to claim 2, characterized in that, The preparation method of the composite sponge includes the following steps: D1. Add nickel nitrate hexahydrate, copper chloride dihydrate, tetraethyl orthosilicate, 2,4-pentanedione and ethanol into a reactor, stir at room temperature for 4 - 6 h to obtain a precursor solution. D2. Perform electrospinning on the precursor solution, and after collecting with a cage-shaped collector, obtain a composite sponge precursor, and perform post-treatment to obtain a composite sponge.
9. A control cable for signal transmission with high shielding performance according to claim 8, characterized in that, In step D1, the dosage ratio of nickel nitrate hexahydrate, copper chloride dihydrate, tetraethyl orthosilicate, 2,4-pentanedione and ethanol is 2 - 3 g: 3 - 4 g: 5 - 6 g: 1 - 2 g: 20 - 24 mL; in step D2, the electrospinning operation is: load the precursor solution into a syringe, extrude it at a rate of 1 - 2 mL / h, the high-speed air flow rate is 10 - 12 m / s, and the distance between the cage-shaped collector and the syringe needle tip is 30 - 50 cm.
Citation Information
Patent Citations
A demagnetizing shielded cable for subway track systems and its preparation method
CN111471301B